2019
DOI: 10.1155/2019/4136295
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Properties and Distribution of Air Voids in Porous Asphalt with Relevance to the Pb(II) Removal Performance

Abstract: In this study, one type of porous asphalt (PA) mixture was designed at two different air void (AV) contents. Direct information regarding both the dimensional properties and AV distribution within two PA specimens in their natural states were observed, compared, and analyzed based on the X-ray CT (computed tomography) and digital image analysis techniques and fractal geometry theory. The characteristics of AV distribution, including AV content, AV number, and AV volume were quantified by comparing pore structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Permeable asphalt (PA) pavement is a popular and practical, low-impact development (LID) technology that serves as an ideal alternative to conventional low-traffic-volume pavement because it can help to address the issues stated above by providing in situ restoration of the urban hydrological cycle and reducing the need for traditional stormwater facilities [28]. PA pavement consists of various layers with porous materials, which not only allow stormwater to infiltrate into the ground, unlike conventional asphalt pavement, but can also simultaneously remove pollutants (e.g., total suspended solids (TSS) and heavy metals) from stormwater runoff on site, thus raising their value as a LID option in current urban development [25,[29][30][31]. As the PA mixture (the surface material of the PA pavement) requires relatively low strength compared to conventional dense asphalt mixtures, researchers have explored the feasibility of recycling MSWI-BA aggregate (MSWI-BAA) in PA mix designs.…”
Section: Introductionmentioning
confidence: 99%
“…Permeable asphalt (PA) pavement is a popular and practical, low-impact development (LID) technology that serves as an ideal alternative to conventional low-traffic-volume pavement because it can help to address the issues stated above by providing in situ restoration of the urban hydrological cycle and reducing the need for traditional stormwater facilities [28]. PA pavement consists of various layers with porous materials, which not only allow stormwater to infiltrate into the ground, unlike conventional asphalt pavement, but can also simultaneously remove pollutants (e.g., total suspended solids (TSS) and heavy metals) from stormwater runoff on site, thus raising their value as a LID option in current urban development [25,[29][30][31]. As the PA mixture (the surface material of the PA pavement) requires relatively low strength compared to conventional dense asphalt mixtures, researchers have explored the feasibility of recycling MSWI-BA aggregate (MSWI-BAA) in PA mix designs.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [5] found that asphalt mixtures with identical air voids may have significantly different performances under given loading and environmental conditions. Zhao et al [6] showed that asphalt mixtures at the same porosity level exhibit different seepage characteristics, and the spatial distribution and direction of voids have an influence on the flow behavior of the mixture. Liu et al [7] tested the mechanical characteristics of asphalt mixtures in different directions and found that the anisotropy of the mixture depends on its internal discontinuous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [7] analyzed the influence of void characteristics on asphalt mixture drainage behavior and noted that void characteristics are the main factor that affects drainage capacity. Zhao et al [8] remarked that asphalt mixture specimens under the same void fraction level exhibit different drainage characteristics, and the distribution and spatial trend of voids affected the drainage behavior. A study by Jiang et al [9] demonstrated that different void equivalent diameters were produced at the same void fraction owing to different grading characteristics, which resulted in significant differences in noise reduction capacity.…”
Section: Introductionmentioning
confidence: 99%